Pengaruh Desain Produk dan Price Fairness Terhadap Minat Beli dan Dampaknya Terhadap Keputusan Pembelian Batik Sepiak Belitong - Lestari; Diyan Lestari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study explains the effect of product design and price fairness on purchase intention and their impact on purchasing decisions of Batik Sepiak Belitong. This research is quantitative research and uses a survey method by using a questionnaire to the respondents. Questionnaires were distributed via google form to 180 respondents which were then analyzed by using SPSS version 25.0. The sampling technique used is purposive sampling. The result of the main test (t-test) shows that product design and price fairness affect the purchase intention, while price fairness has no effect on purchase intention or purchasing decisions, then product design and purchase intention affect purchase decisions for Batik Sepiak Belitong.